Review on Synergistic Effects of Probiotics, Prebiotics, and Synbiotics on Gut Microbiota Homeostasis - Murtaza, Ghulam; Abbas, Zaighum; Gul, Sabeen; Karam, Asfa; Cheema, Nadia; Zahra, Maham; Abbas, Sarwat; Ali, Fazil; Kabir, Abdul; Shah, Muhammad Kamal; Sajid, Muhammad (Indus Journal of Bioscience Research, 2024)
Functional foods are an essential part of the contemporary diets, and it is evident that these foods contain the health benefits in addition to the familiar nutritional effects. Probiotics and prebiotics together is referred to as synbiotics and are presently the most popular functional food ingredients. The most commonly used probiotic strains are Lactobacilli, Bifidobacterium, S. boulardii and B. coagulans. Some of the most used fibers are galacto-oligosaccharides (GOS), fructo-oligosaccharides (FOS), xylose-oligosaccharide (XOS), inulin, and fructans when blended with probiotics are referred to as synbiotics and are efficient in provoking the growth of the bacteria.